Pre-Chemotherapy Differences in Visuospatial Working Memory in Breast Cancer Patients Compared to Controls: An fMRI Study - Scherling, Carole S.; Collins, Barbara; MacKenzie, Joyce; Bielajew, Catherine; Smith, Andra (Frontiers in Human Neuroscience, 2011)
Introduction: Cognitive deficits are a side-effect of chemotherapy, however pre-treatment research is limited. This study examines neurofunctional differences during working memory between breast cancer (BC) patients and controls, prior to chemotherapy. Methods: Early stage BC females (23), scanned after surgery but before chemotherapy, were individually matched to non-cancer controls. Participants underwent functional magnetic resonance imaging (fMRI) while performing a Visuospatial N-back task and data was analyzed by multiple group comparisons. fMRI task performance, neuropsychological tests, hospital records, and salivary biomarkers were also collected. Results: There were no significant group differences on neuropsychological tests, estrogen, or cortisol. Patients made significantly fewer commission errors but had less overall correct responses and were slower than controls during the task. Significant group differences were observed for the fMRI data, yet results depended on the type of analysis. BC patients presented with increased activations during working memory compared to controls in areas such as the inferior frontal gyrus, insula, thalamus, and midbrain. Individual group regressions revealed a reverse relationship between brain activity and commission errors. Conclusion: This is the first fMRI investigation to reveal neurophysiological differences during visuospatial working memory between BC patients pre-chemotherapy and controls. These results also increase the knowledge about the effects of BC and related factors on the working memory network. Significance: This highlights the need to better understand the pre-chemotherapy BC patient and the effects of associated confounding variables.